The efficacy of adjunct tacrolimus treatment in pregnancy outcomes in patients with systemic lupus erythematosus. (July 2018) - Ichinose, K; Sato, S; Kitajima, Y; Horai, Y; Fujikawa, K; Umeda, M; Fukui, S; Nishino, A; Koga, T; Kawashiri, S Y; Iwamoto, N; Tamai, M; et al.
Systemic lupus erythematosus (SLE) involves multiple organ systems and primarily affects women during their reproductive years. Pregnancy in a woman with SLE may lead to higher rates of disease flares. Little is known regarding which medications are safe to maintain remission and/or treat flares throughout such pregnancies. Here we retrospectively analyzed the efficacy of tacrolimus (TAC) in the pregnancy outcomes of SLE patients. We studied the 54 deliveries of 40 SLE patients over an eight-year period from 2008 to 2016. We used analyses of covariance with adjustments for the propensity score and inverse probability of treatment weights to compare the patient backgrounds between the TAC users and non-TAC users. TAC was administered to the patient in 15 of the 54 (27.8%) pregnancies, and these patients had a significantly higher dose of prednisolone, hypocomplementemia, lower estimated glomerular filtration rate, past history of lupus nephritis, and complication with antiphospholipid syndrome. In the adjusted background of the TAC deliveries, the risks of decreased fetal body weight, low birth weight infant, non-reassuring fetal status (NRFS), and preterm birth were not increased compared to the non-TAC deliveries. Thrombocytopenia and hypertension during the pregnancy were extracted as independent predictive risk factors for decreased fetal body weight and NRFS, respectively. We had anticipated that the maternal and fetal outcomes in the TAC-use deliveries would be poor before the analysis; however, the TAC-use group showed no significant difference in risks contributing to outcomes compared to the non-TAC group, suggesting that adjunct TAC treatment corrected various risk factors during the lupus pregnancies.